Improving Student Learning Outcomes Through Problem Based Learning Models in Indonesian Language Subjects for Elementary School Students - Arsad Arsad; Muhammad Yusnan (Institute Journal and Publication Muhammadiyah University of Buton, 2023)
This research aims to improve student learning outcomes through the Problem Based Learning (PBL) learning model in Indonesian language learning in Class V of Wameo 2 State Elementary School. This type of research is classroom action research, each cycle consisting of 4 stages, namely planning, action, observation and reflection. The research subjects chosen were 16 students in class V of Wameo State Elementary School 2, even semester of the 2021/2022 academic year, consisting of 10 male students and 6 female students. The data collection techniques used were observation, test sheets, interviews and documentation. Based on the research results in cycle I and cycle II, results were obtained which showed an increase in learning outcomes, namely from the test results in cycle I there were 10 students who completed (62.50%) and 6 students (37.50%). Incomplete with an average score of 65. .62. Student learning outcomes in cycle II were 14 students (87.50%) completed and 2 students (12.50%) incomplete with an average score of 92.5. The results of this research indicate that the use of the Problem Based Learning learning model can improve student learning outcomes from cycle I to cycle II.